Strategi Pengembangan Pemasaran Digital Menggunakan Aplikasi Blogger pada UMKM Atceare Essensial Oil di Kota Padang - Fitri Fadila; Yudha Ananda; Raihana Mardhiyyah; Sularno; Rafidola Mareta Riesa (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
With the rapid development of technology and social media, MSMEs are faced with new opportunities and challenges in marketing their products. Competition in the business world is increasingly fierce, making entrepreneurs look for the right strategy to market their products. One of them is using digital in the marketing and sales process, and marketing in the form of creating a website using the Blogger application. This research focuses on Atceare Essential Oil MSMEs which are engaged in the sale of essential oils. The research results show that using Blogspot provides benefits such as expanding market reach and interaction with customers. The research method used is a case study with a qualitative approach, involving in-depth interviews. It is hoped that this research can provide practical guidance to MSMEs in utilizing Blogspot as an effective promotional tool in the digital era, as well as contributing to sustainable local economic growth in facing market competition and achieving sustainable growth..